2008
DOI: 10.3844/ajavsp.2008.40.42
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Seroprevalence of Anti-Toxoplasma Gondii Antibodies in Cattle in Tabriz (Iran) by IFAT

Abstract: Toxoplasmosis is a zoonotic disease in various species of animals caused by a sporozoan parasite, Toxoplasma gondii. The disease occurs throughout the world including Iran. This disease is a common infection of sheep, goats and it is recognized as one of major infection cause of reproductive failure. This survey was carried out to show the prevalence of this disease in cattle in Tabriz (Iran). 490 sera samples were collected from both native and industrial cattle. The Indirect Fluorescent Antibody Test (IFAT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 6 publications
7
14
0
Order By: Relevance
“…Positive cases were more frequent among cattle less than one year old (36.4%, P < 0.05) than cattle above two years old. This is in concordance with Nematollahi and Moghddam [2] who reported similar results in Iran in 2008. This may reflect dominance of maternally acquired antibodies in this age group or that the cattle unless reinfected, deplete antibodies as their age increases [3].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Positive cases were more frequent among cattle less than one year old (36.4%, P < 0.05) than cattle above two years old. This is in concordance with Nematollahi and Moghddam [2] who reported similar results in Iran in 2008. This may reflect dominance of maternally acquired antibodies in this age group or that the cattle unless reinfected, deplete antibodies as their age increases [3].…”
Section: Discussionsupporting
confidence: 92%
“…The overall seroprevalence of toxoplasmosis reported in the present study in Sudan using ELISA (13.3%) is higher than that reported for cattle in China (2.3%) [18] and Vietnam (10.5%) [19] but is comparable to that reported in Iran (15.91%) [2] and lower than that (27.9%) recorded in The Netherlands [20]. The differences in prevalence rates between countries may be due to the samples size of different studies besides the different techniques used.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Rozette et al (2005) report a similar finding in contrast to those of El fahal et al (2013) who found a higher seroprevalence in cattle aging less than 1 year, thing that could be explained by the capacity of this species to eliminate the parasite with age. The distribution of seroprevalence according to gender showed no significant difference what is in agreement with the reports of Klun et al (2006) and Garcia et al (1999); however, those of Nematollahi and Moghddam (2008) showed that seropositivity is higher among males. The low antibody titer of 1:64 suggests that toxoplasmosis spreads in these farms in a latent form; it is similar to the findings of Santos et al (2013).…”
Section: Discussionsupporting
confidence: 90%
“…The higher seroprevalence observed in large herd size is similar to observations made by several researchers (Ghazaei 2005;2006;Teshale et al 2007). According to one finding, large herd size enhances the exposure potential, through increased contact at common feeding and watering points contaminated with sporulated T. gondii oocysts shed by infected domestic cats or wild felines (Nematollahi and Moghddam 2008). There are no reports on toxoplasmosis in livestock in Tanzania with which to compare the results of this CI lower and upper limits for 95% confidence interval of the seroprevalence study.…”
Section: Discussionmentioning
confidence: 93%